2020
DOI: 10.15282/jmes.14.4.2020.11.0585
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the flexural properties of nanofillers loading on the Jute/Carbon/PLA nanocomposites

Abstract: Presence of fibers and fillers in a composite can be an efficient way to arrest crack either at macro or micro levels. In this work, woven jute and carbon fibers were arranged alternately in PLA (Polylactic Acid) nanocomposite. Graphene or nanoclay was embedded into PLA matrix to make polymer nanocomposite. Fiber reinforced polymer nanocomposites were prepared by varying the concentration of graphene or nanoclay in the PLA matrix and alternate woven jute/carbon fibers was then bind with the PLA nanocomposite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…They concluded that bamboo fiber composites with CNT nanofillers could be used for a wide range of applications, including automotive parts, building and construction materials, and electrical and electronic components. In a recent study by Sairy et al, 7 researchers investigated the influence of graphene nanofillers on the characteristics of jute fiber composites. They found that the addition of graphene significantly enhanced the tensile strength, modulus, and thermal stability of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that bamboo fiber composites with CNT nanofillers could be used for a wide range of applications, including automotive parts, building and construction materials, and electrical and electronic components. In a recent study by Sairy et al, 7 researchers investigated the influence of graphene nanofillers on the characteristics of jute fiber composites. They found that the addition of graphene significantly enhanced the tensile strength, modulus, and thermal stability of the composites.…”
Section: Introductionmentioning
confidence: 99%